Non-endoscopic Examination as Predictor of Varices Degree in Liver Cirrhosis Patients Who have Experienced Esophageal Variceal Bleeding - Paulus Kusnanto; Marcellus Simadibrata; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2011)
Background: Standard diagnosis for determining the degree of varices is by endoscopy. However, sometimes there are obstacles in the implementation of endoscopy. Based on the factors, we need to know the parameters of non-endoscopic examination which include ascites, splenomegaly, thrombocytopenia, Child-Pugh, portal vein diameter as a predictor of the degree of liver cirrhosis patients with varices who have experienced esophageal variceal bleeding. Method: The study design was cross-sectional study. The study was conducted on hospitalized patients in Cipto Mangunkusumo hospital, Gatot Subroto hospital, and Kraton hospital from September 2008 to November 2009. The patients were liver cirrhosis patients with history of upper gastrointestinal bleeding, no present bleeding, and hemodynamically stable. Examination of predictor factors in the patients such as ascites, splenomegaly, thrombocytopenia, Child-Pugh and portal vein diameter were done. Statistical analysis was performed with student’s t-test, Mann-Whitney test, and stepwise multivariable logistic regression. Results: The study involved 44 patients with liver cirrhosis who have esophageal variceal bleeding. Based on the results of endoscopic examination, large varices (F3) were found in 21 (47.73%) patients, small varices (F1 F2) in 23 (52.27%) patients, located on the distal esophagus extending to the medial (86.4%), with red color sign present (54.5%). Results of non-endoscopic examination such as splenomegaly, ascites, thrombocytopenia, portal vein diameter and Child-Pugh score was known not to be associated with the degree of esophageal varices (p 0.05). Conclusion: Non-endoscopic examination was not related to the degree of varices in liver cirrhosis patients who have experienced esophageal variceal bleeding. Keywords: esophageal variceal bleeding, liver cirrhosis, predictor factors, endoscopic criteria